THE ROLE OF MOTIVATION AND JOB SATISFACTION IN IMPROVING THE PERFORMANCE OF TEACHERS AND EMPLOYEES IN EDUCATIONAL INSTITUTIONS - Aryani, Anik; Rindaningsih, Ida (Antis-Publisher, 2024)
Objective: This study aims to identify the key components influencing teacher performance and employee satisfaction in educational environments. Method: A systematic literature review was conducted to analyze the relationship between work motivation, Human Resource (HR) strategies, and workplace conditions with teacher performance and job satisfaction. Results: The study reveals that work motivation significantly enhances teacher performance, leading to increased job satisfaction and productivity. Strategic HR planning contributes to optimal employee performance, while a supportive work environment improves work ethic and motivation, albeit with inconsistent effects on job satisfaction. Furthermore, a fair and performance-based compensation system, along with non-financial rewards, is essential for maintaining motivation and improving performance. Novelty: This research provides actionable strategic recommendations for educational institutions, emphasizing the importance of enhancing work motivation, implementing effective HR planning, and fostering a conducive work environment to boost teacher performance and satisfaction.